Assessment of Women Seeking Medical Termination of Pregnancy in a Tertiary Care Hospital, India - Kakkar, Ankita; Rastogi, Pooja; Saxena, Anshul; Bharti, Rohit (Research Highlights in Disease and Health Research Vol. 5, 2023)
This study is conducted to assess the existing scenario of Medical Termination of Pregnancy cases and the sociodemographic profile of such cases presenting to a Tertiary care Hospital. Since time immemorial, abortion was and still remains an important health concern of women across India .Induced abortion whether safe or unsafe, legal or illegal is a reproductive health service that is part of the lives of several women all across the country. Despite that there is a dire need for a sense of independence to exercise her rights to take exclusive decision of terminating or continuing her pregnancy, the fact remains that termination of pregnancy in India is to be conducted as stipulated in the MTP Ac. The Act often limits the freedom of women who come to seek abortion as a right. In this backdrop the present study was undertaken with the objective to study socio-demographic profile, methods and various indications in the reported Medical Termination of Pregnancy cases.